Quantifying the value teachers place on non-monetary factors when evaluating job opportunities - Gunther, Jeffrey (Education Policy Analysis Archives, 2019)
The way in which working conditions, personal characteristics, and school factors influence teacher recruitment and retention is an oft-studied topic in the field of education finance and policy. Through decades of research, it has become increasingly clear that teachers respond to a set of monetary and non-monetary factors when making decisions in the teacher labor market. What is less clear is the relative or absolute value teachers place on factors such as salary, student demographic factors, school conditions, and other working conditions such as class size, curricular autonomy, and principal support, to name a few. This project introduces the use of a novel survey methodology to the field to aim to answer these questions. This study utilizes Adaptive Choice-Based Conjoint (ACBC) analysis to quantify the relative importance of various monetary and non-monetary job factors to practicing teachers as they consider the desirability of various hypothetical schools. The use of ACBC in an estimate of the value placed on various working condition factors by secondary teachers in Utah and an analysis of how those valuations vary with personal and demographic factors. The results of this research provide practical recommendations for administrators and policymakers that aim to make schools more desirable for teachers and demonstrates the use of a novel methodology to answer outstanding questions in the field of teacher recruitment and retention.